2021
DOI: 10.1039/d0na00904k
|View full text |Cite
|
Sign up to set email alerts
|

A review on the cytotoxicity of graphene quantum dots: from experiment to simulation

Abstract: Schemetic diagram of the mechanism of GQD-induced cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 88 publications
1
26
0
Order By: Relevance
“…In terms of decision-making, Because of nomenclature perplexity, the data available on CDs cytotoxicity is very confused. Even in the latest reviews various CDs having different topology, composition and sizes are commonly considered as GQDs, [78][79][80] which is wrong. It seems small spherical CNDs are less cytotoxic than plane large GQDs, probably due to different permeability and transport mechanisms.…”
Section: Cytotoxicity Of N-goqdsmentioning
confidence: 99%
“…In terms of decision-making, Because of nomenclature perplexity, the data available on CDs cytotoxicity is very confused. Even in the latest reviews various CDs having different topology, composition and sizes are commonly considered as GQDs, [78][79][80] which is wrong. It seems small spherical CNDs are less cytotoxic than plane large GQDs, probably due to different permeability and transport mechanisms.…”
Section: Cytotoxicity Of N-goqdsmentioning
confidence: 99%
“…S3 and S4, ESI †) showed that GQDs drastically reduced the proliferation of the cells and induced phenotypic changes such as fragmentation of cell wall, cell contraction, cell displacement from the monolayer surface, and formation of a round or oblong mass of cytoplasm compared with untreated cells, demonstrating events that are associated with apoptosis. 31,58 GQDs mediate apoptotic morphology in MDA-MB-231 and MCF-07 cells Apoptosis is the primary cell death mechanism in response to the cytotoxic effect. These are often associated with cellular and phenotypical changes such as chromatin condensation, membrane blebbing, cleavage of key proteins and DNA fragmentation.…”
Section: Cytotoxicity Studies Of Gqdsmentioning
confidence: 99%
“…If properly designed and formulated, they can improve the polymer’s thermal and mechanical barriers and its flammability properties [ 32 ]. Surface charge density, doping status, the degree of surface oxidation, or inks with polymers are among the properties of GQDs that can cause different interactive behaviors with biomolecules and which are dramatically different in additional others [ 33 ]. The elastomer matrix is combined with filler properties such as nanoparticles or graphene by flexible and durable polymer composites.…”
Section: Introductionmentioning
confidence: 99%